Tendrá obligación de llevar un diario de campaña: representaciones de Género y Etnicidad en registros documentales sobre los mapuche, durante la segunda mitad del siglo XIX - Elsa Gabriela González-Caniulef (Nuevo mundo - Mundos Nuevos, 2015)
This paper analyzes the presence and use of the categories of gender and ethnicity on hegemonic discourses about the mapuche people in the second half of the nineteenth century in Chile. Two kinds of sources were addressed -photography and classic historiography- paying special attention to the way in which narratives about the mapuche people, and particularly about mapuche women, were reconfigured according to the mentioned cateories.